Pengembangan Virtual Laboratorium Sentrifusi pada Pembelajaran Berbasis Proyek sebagai Media Pembelajaran untuk Meningkatkan Hasil Belajar Mahasiswa - Sirumapea, Mutiara Sani; Situmorang, Manihar (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2025)
Chemistry learning on the topic of separation through the centrifuge process in higher education has not been implemented through practical work, due to the limited availability of relevant laboratory activities. As a result, centrifuges are rarely used and students do not understand how to operate them. This condition causes the learning process to focus on delivering theory without practical experience, so that students' understanding of the concept of centrifuges becomes shallow and has an impact on low learning outcomes. This study aims to develop a virtual centrifuge laboratory learning media based on assignment projects in the form of questions, and to improve student learning outcomes. The method used is Research and Development (R&D) with the ADDIE model. The research subjects consisted of 34 students of the Chemistry Study Program. The research instruments included a non-test instrument in the form of a media expert validation questionnaire, as well as a test instrument in the form of pre-test and post-test questions. The validation results showed that the learning media was classified as